Environmental monitoring and characterization - Artiola, Janick F; Pepper, Ian L; Brusseau, Mark L (Elsevier Academic Press, 2004)
Environmental Monitoring and Characterization is an integrated, hands-on resource for monitoring all aspects of the environment. Sample collection methods and relevant physical, chemical and biological processes necessary to characterize the environment are brought together in twenty chapters which cover: sample collection methods, monitoring terrestrial, aquatic and air environments, and relevant chemical, physical and biological processes and contaminants. This book will serve as an authoritative reference for advanced students and environmental professionals. * Examines the integration of physical, chemical, and biological processes* Emphasizes field methods and real-time data acquisition, made more accessible with case studies, problems, calculations, and questions* Includes four color illustrations throughout the text* Brings together the concepts of environmental monitoring and site characterization